Salvia (Lamiaceae) is not monophyletic: implications for the systematics, radiation, and ecological specializations of Salvia and tribe Mentheae - Walker, Jay B.; Treutlein, Jens; Wink, Michael (American journal of botany, 2004)
Salvia, with over 900 species from both the Old and New World, is the largest genus in the Lamiaceae. Unlike most members of the subfamily Nepetoideae to which it belongs, only two stamens are expressed in Salvia. Although the structure of these stamens is remarkably variable across the genus, generally each stamen has an elongate connective and divergent anther thecae, which form a lever mechanism important in pollination. In a preliminary investigation of infrageneric relationships within Salvia, the monophyly of the genus and its relationship to other members of the tribe Mentheae were investigated using the chloroplast DNA regions rbcL and trnL-F. Significant conclusions drawn from the data include: Salvia is not monophyletic, Rosmarinus and Perovskia together are sister to an Old World clade of Salvia, the section Audibertia is sister to subgenus Calosphace or the monotypic Asian genus Dorystaechas, and the New World members of section Heterosphace are sister to section Salviastrum. Owing to the non-monophyly of Salvia, relationships at the next clearly monophyletic level, tribe Mentheae, were investigated.